Influência do comprimento do parafuso nas propriedades biomecânicas da placa de reconstrução bloqueada - Santos, Rogerio Rodrigues [UNESP] (2015)
The aim of this study was to evaluate the influence of screw length, mono or bicortical, on the mechanical properties of a locking reconstruction plate. Sixty cylinders of synthetic bone and 60 seven-hole 3.5 mm locking reconstruction plates were used. Each cylinder of synthetic bone was equally divided to simulate a gap fracture of 10 mm. Two groups of bone-plate constructs were mounted: Group 1 - three monocortical screws in each fracture side, Group 2 - three bicortical screws in each fracture side. In both groups, the area of the fracture gap was maintained without screw. To establish the loads for fatigue testing, for each group nine bone-plate constructs were tested until failure, each three in compression, bending, and torsion. For each group, 21 bone-plate constructs were tested for failure in fatigue testing, each seven in compression, bending, and torsion. By statistical analysis, significant differences between groups were observed for axial compression fatigue testing (G1>G2) and fourpoint bending fatigue testing (G1<G2) and in maximum load, minimum load, maximum moment, and minimum moment. No significant differences were observed between groups for torsion fatigue testing. In conclusion, the screw length can affect the mechanical properties of locking reconstruction plate